Doctrinal (Conceptual) Errors: General Theoretical Aspect - Vladimir Valentinovich Kozhevnikov (Polit Journal Scientific Journal of Politics, 2025)
This scientific article examines the problem of the relationship between doctrinal (conceptual) and law-making legal errors. The concept of legal error is considered and its symptoms are analyzed. Attention is paid to the characteristics of doctrinal errors, their characteristics, among which the most important is their political and ideological nature. Analysis of the legal literature made it possible to identify two approaches to solving the problem posed. Proponents of the first approach, both representatives of the general theory of law and branch sciences, believe that doctrinal errors are types of law-making errors. Being embodied in a normative legal act, they are also law-making errors. The author supports the more substantiated position of supporters of the second approach, who, distinguishing between doctrinal and law-making errors, believe that the first can arise at the stage of the process of cognition of objective laws that lie outside the law-making process; that doctrinal errors are a prerequisite for law-making errors. In conclusion, attention is drawn to the important role of legal science in preventing doctrinal errors.